Closing the Dream Gap: An Implementation Science Blueprint for Statewide Postsecondary Support for Youth with Foster Care Experience. - Greeson, Johanna K. P. (Child Welfare, 2026)
Youth with foster care experience face steep barriers to higher education due to inequities, disrupted schooling, and limited supports. In 2022, more than 19,000 children and youth--about one third of them transition-age youth--were placed in Pennsylvania's foster care system. Yet too few of these youth go on to complete a postsecondary credential. This article presents the Foster Care to College (FC2C) initiative, the first statewide model grounded in implementation science in Pennsylvania. Using an integrated logic model and core components framework, we describe FC2C's theory of change, key activities, and outcomes, off ering a replicable blueprint to advance equity and help close the foster care "Dream Gap.